2013
DOI: 10.1111/ejn.12112
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of the dopamine D1‐like receptor in mesocorticolimbic nuclei attenuates acute food deprivation‐induced reinstatement of heroin seeking in rats

Abstract: The neurotransmitter dopamine (DA) plays a critical role in both priming-and cue-induced reinstatement of extinguished drug-seeking behavior, but its role in stress-induced reinstatement is less clear. Our laboratory has recently demonstrated that systemic administration of the DA D1-like receptor antagonist, SCH 23390, attenuates acute food deprivation (FD) stress-induced reinstatement. The current study was designed to elucidate the brain regions critical to the effect of SCH 23390 on FD stress-induced reins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Previous studies suggest that DA D1-like receptors are important for context-and discriminative cue-induced reinstatement of heroin, cocaine, and natural rewards seeking . Moreover, we have recently reported that blockade of DA D1-, but not D2-like receptors, attenuated acute food deprivation-induced reinstatement of heroin seeking (Tobin et al, 2013). In addition, chronic food restriction increases synaptic plasticity in NAc cells expressing DA D1-like, but not D2-like, receptors (Carr et al, 2003(Carr et al, , 2010.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies suggest that DA D1-like receptors are important for context-and discriminative cue-induced reinstatement of heroin, cocaine, and natural rewards seeking . Moreover, we have recently reported that blockade of DA D1-, but not D2-like receptors, attenuated acute food deprivation-induced reinstatement of heroin seeking (Tobin et al, 2013). In addition, chronic food restriction increases synaptic plasticity in NAc cells expressing DA D1-like, but not D2-like, receptors (Carr et al, 2003(Carr et al, , 2010.…”
Section: Introductionmentioning
confidence: 92%
“…For rats in the microdialysis experiments, unilateral guide cannulae, counterbalanced between the right and left hemispheres, were implanted targeting the NAc shell (Experiment 1) or NAc core (Experiment 2) during the intravenous surgical procedure (Ito et al, 2000). For DA receptor antagonist administration, bilateral guide cannulae targeting the NAc shell (Experiment 3) or NAc core (Experiment 4) were implanted during the intravenous surgical procedure (Tobin et al, 2013). See also Supplementary Material.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Tobin et al (2013) recently performed a comprehensive study assessing the role of dopamine D1 receptors in different brain regions in acute 1-day food-deprivation-induced reinstatement of heroin seeking. They found that injections of the D1-family receptor antagonist SCH 23390 into accumbens shell, dorsal mPFC, and basolateral amygdala, but not accumbens core or ventral mPFC, decrease this reinstatement (Tobin et al 2013). An interpretation issue in this study is that SCH 23390 is also a 5-HT2C (formerly 5-HT1C) receptor agonist (Millan et al 2001).…”
Section: Recent Neurobiological Findingsmentioning
confidence: 99%
“…Intracranial infusion of SCH-23390, an antagonist for dopamine D 1 -like receptors (including D 1 and D 5 receptors), into the prelimbic cortex potently and dose dependently attenuated heroin seeking in response to either cue presentations or a priming dose of heroin, suggesting that D 1 receptors regulate prefrontal pathways necessary for the reinstatement of heroin seeking (See, 2009). Attenuated reinstatement of heroin seeking was observed in rats injected with SCH-23390 into the NAc shell, suggesting that dopamine transmission in the NAc through the D 1 -like receptors plays a critical role in the drug reinforcement and motivational drive that promotes drug-seeking behavior (Tobin et al, 2013). Studies also revealed an attenuation of drug seeking following systemic administration of the D 3 receptor antagonist, SB-277011A (Xi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%